Pengaruh model Course Review Horey terhadap hasil belajar matematika - Huda, Iin Inarotul; Azhar, Ervin; Kurniawan, Yunda (Program Studi Pendidikan Matematika, FKIP, Universitas Siliwangi, Tasikmalaya, 2018)
The purpose of this research to know the influence of using model Course Review Horey to the result of student’s mathematics learning. This research is Quasi Experimental Design type. This sampling technique used purposive sampling with 76 students at SMP Negeri 1 Sepatan in 8 class in the even semester of the school year 2017/2018. The research instrument is result of student’s mathematics learning test that shaped essay as many as 7 questions item, that have been validity test, reliability test, level of difficulty test and distinguishinhing power test. The requirements analysis test that normality test using Lilliefors test and homogeneity test using Fisher test. Based on requirements analysis test found both classes are normally distributed and homogenenous variants. Hypothesis test using t-test and is rejected. Thus, there is an influence in model Course Review Horey to the result of student’s mathematics learning.Keyword : Course Review Horey model’s; result of student’s, mathematics.